Internalizing ‘Iffah Values to Foster Islamic Character among iGeneration Students - Putu Muchtar, Nicky Estu; Crisnasari, Nihaya Alifiya (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2026)
The rapid advancement of digital technology and globalization has exposed iGeneration students to increasingly complex moral challenges, highlighting the need for effective character education grounded in Islamic values. Although previous studies have discussed ‘iffah primarily from theological and conceptual perspectives, limited empirical evidence explains how this value is internalized through educational practices to foster Islamic character among students in the digital era. This study aims to examine the process of ‘iffah value internalization, identify the supporting and inhibiting factors, and analyse its implications for developing Islamic character among iGeneration students at SMK Islam Bustanul Hikmah Kembangbahu Lamongan. Employing a qualitative case study approach, data were collected through observations, in-depth interviews, and documentation, and analysed using the interactive model of Miles and Huberman. The findings reveal that ‘iffah value internalization occurs through three interconnected stages: value transformation, value transaction, and transinternalization. The process is strengthened by school policies, teachers’ role modelling, and a religious school environment, while social media influence, peer interactions, and family background remain significant challenges. The internalization of ‘iffah values contributes to strengthening students’ self-control, preserving personal dignity, and fostering Islamic character in both offline and digital contexts. The novelty of this study lies in providing empirical evidence of how school-based character education internalizes ‘iffah values among iGeneration students in the digital era, thereby enriching the discourse on Islamic character education through a contextual and practice-oriented perspective.